Towards a non-violent revolution - Desai, Narayan (Sarva Seva Sangh Prakashan, 1972)
On the performance of the Shanti Sena, Gandhian social service movement founded in 1962 by Vinoba Bhave, 1895-, in tackling Indian social problems.